2010
DOI: 10.1111/j.1365-2648.2010.05303.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Learning Environment Inventory: factor analysis

Abstract: The study offers an empirically based and theoretically informed extension of the original Clinical Learning Environment Inventory, which had previously relied on ad hoc clustering of items and the use of internal reliability of its sub-scales. Further research is required to establish the consistency of these new factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(109 citation statements)
references
References 31 publications
5
102
1
1
Order By: Relevance
“…The items reported as more satisfied were their feeling of well preparation for the required The study' results are supported with [37] and [38] who reported students satisfaction with placement mainly because they met their placement objectives, enjoyed their time and worked as a team who are willing and available staff that assisted them in learning. Studies conducted by [39] and [17] indicated that all students, regardless of location, rated higher satisfaction with their clinical experiences.…”
Section: Discussionsupporting
confidence: 51%
“…The items reported as more satisfied were their feeling of well preparation for the required The study' results are supported with [37] and [38] who reported students satisfaction with placement mainly because they met their placement objectives, enjoyed their time and worked as a team who are willing and available staff that assisted them in learning. Studies conducted by [39] and [17] indicated that all students, regardless of location, rated higher satisfaction with their clinical experiences.…”
Section: Discussionsupporting
confidence: 51%
“…Most researchers emphasized the CLE as composed of multiple entities having an impact on student learning and highlighting student achievement of outcomes is not guaranteed after having CLE experiences (Dunn & Burnett , Levett‐Jones & Lathlean , Sand‐Jecklin , Newton et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…Variations about educational preparation of instructors were noted, with some being faculty and having graduate level education about pedagogy and learning theories and others being staff nurses with no description of educational preparation (Dunn & Burnett , Chan , Saarikoski & Leino‐Kilpi , Hosoda , Newton et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…Clinical practice is a crucial part of a nurse's education and clinical competence development (Flott & Linden, ; Jokelainen, Turunen, Tossavainen, Jamokeeah, & Coco, ), as it shapes nursing students' professional role, behaviour, attitudes and values (Newton, J. M., Jolly, Ockerby, & Cross, ; Sandvik, Eriksson, & Hilli, ). Clinical environments are multidimensional and described as physical and psychosocial spaces with complex organisational cultures and learning settings (Flott & Linden, ).…”
Section: Introductionmentioning
confidence: 99%